2021
DOI: 10.1088/1755-1315/910/1/012093
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Phenolic Contents of Fresh and Concentrated Juice of Four Pomegranate Cultivars in Iraq

Abstract: In this study, four pomegranate cultivars were selected in Halabja City. Their physical properties such as peel, arils, juice, seed, and juice concentrate percentage, chemical properties, and some phenolic and sugars compounds of the juices and juices concentrate was compared among all cultivars. Of all four cultivars (Wonderful, Swra hanar, Salakhani, and Kaua hanar), Wonderful and Salakhani presented the highest pH values in juice and juice concentrate and they obtained a signififcant percentage of juice con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Conversely, calcium levels were higher in fresh juices, possibly due to the degradation of binding agents during storage. The comparative analysis of the three varieties indicated that Ghandhri juice had higher zinc content, while Tarnab Gulabi juice showed superior iron levels, illustrating the significant varietal effects on mineral composition in pomegranates (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, calcium levels were higher in fresh juices, possibly due to the degradation of binding agents during storage. The comparative analysis of the three varieties indicated that Ghandhri juice had higher zinc content, while Tarnab Gulabi juice showed superior iron levels, illustrating the significant varietal effects on mineral composition in pomegranates (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…The fruits of the Salakhani cultivar have been described as medium to large in size and have a thick reddish-yellow peel saturated with pink. Moreover, the arils are red to pink and juicy, it taste sour-sweet with good flavor, and the fruits of this cultivar are the most important for export in Kurdistan Iraq (4,1). Therefore, the present study aimed to evaluate the effect of coating with flaxseed, black seed oil, and chitosan in maintaining the storage quality characteristics and prolong the storage period and shelf life of the "Salakhani" pomegranate fruits…”
Section: ‫العراقية‬ ‫الزراعية‬ ‫العلوم‬ ‫مجلة‬mentioning
confidence: 99%
“…Fruit contains a lot of saccharides, polyphenols, and essential minerals. The physical and chemical properties of pomegranate have been evaluated in Turkey and Italy [4,5]. The peel (pericarp), seeds, and aril (around the seeds) comprise the fruit.…”
Section: Introductionmentioning
confidence: 99%